MANAJEMEN PENDIDIKAN ISLAM DALAM MENINGKATKAN KEDISIPLINAN SANTRI DI PONDOK PESANTREN SALAFIYS WHUSTHO (PPS) AN NI’MAH KEC SAGULUNG KEL SUNGAI PELUNGUT BATAM KEPRI - Dessi, Dessi (UNISAN JURNAL, 2024)
Discipline is obedience to respect and implement a system that requires people to submit to applicable decisions, orders and regulations. The aim of this research is to find out how Islamic education management planning improves the discipline of students at the Salafiys whustho Islamic boarding school (PPS) An ni’mah. This research uses descriptive qualitative research methods. This research is field research using techniquesdata collection, observation, interviews and documentation. The data analysis technique uses analysis in Islamic Education Management in Improving the Discipline of Santri at the Salafiys whustho Islamic Boarding School (PPS) An ni’mah. The field findings in this research are: the implementation of character education at PPTQ Mutiara Sunnah Palembang is competent The main things that every teacher masters are; The RPP regulates competencies, curriculum implementation and evaluation. So, the implementation of character education for each lesson is through: creating graduate competency standards (SKL), preparing standards (SK), preparing learning indicators, learning evaluation strategies, implementing all these improvements with supporting factors and limiting factors. This means that the implications of the research are that every teacher must have professionalism, be a good worker, have fresh functions and credible performance. This means that implementing character education is education with aspects of building morals, (ethics-aesthetics), cognition, feelings and psychomotor actions.